Soybean protein / polyvinyl alcohol-dopamine composite water treatment material with sponge structure

By developing soy protein/polyvinyl alcohol-dopamine composite water treatment materials with sponge structure, the existing adsorbents have been solved, and the problems of small adsorption capacity and difficulty in recycling are achieved, and the advantages of high efficiency of adsorption of oils and dyes are achieved, and environmentally friendly, low cost and reusable are provided.

CN119701897AActive Publication Date: 2025-03-28GUANGDONG UNIV OF TECH

Patent Information

Application Number
CN202411923764.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing water-treated adsorbents have problems with small adsorption capacity, difficulty in recycling and easy to breakage, and biomass-based adsorbents have not yet fully utilized their potential in practical applications.

Method used

A soy protein/polyvinyl alcohol-dopamine composite water treatment material with a sponge structure is developed to form a three-dimensional interoperable porous material through freeze-drying and soaking treatment, which improves adsorption capacity and reusability.

Benefits of technology

It has achieved efficient adsorption of oil and dye pollutants, and has the advantages of environmentally friendly, low cost and reusable, with high pore ratio and large pore surface area, which is suitable for large-scale production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701897A_ABST
    Figure CN119701897A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of bio-based water treatment materials, in particular to a soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure, which is prepared by the following steps: step 1, preparing carboxylated polyvinyl alcohol; 2, introducing dopamine hydrochloride to react with the polyving akohol solution to obtain a dopamine grafted polyving akohol solution; step 3, performing dialysis and rotary evaporation concentration treatment on the dopamine grafted polyvinyl alcohol solution to obtain a dopamine grafted polyvinyl alcohol concentrated solution; 4, soybean protein isolate is added into the dopamine grafted polyvinyl alcohol concentrated solution, and a compound is obtained after freeze drying; and step 5, putting the compound into an n-hexane solution of methyltrimethoxysilane for soaking, and finally drying in a drying oven to obtain the soybean protein / polyvinyl alcohol-dopamine composite water treatment material with the sponge structure. The material is environment-friendly, has an elastic and porous structure, can repeatedly adsorb oil products, and has selective adsorption on cationic dyes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bio-based water treatment materials, and in particular to a soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure. Background Art

[0002] Pollution of aquatic systems causes diseases and even death in humans, plants, and organisms worldwide. To improve environmental sustainability, reasonable and effective wastewater management is needed. Water must be purified to a level that is safe for drinking, washing, and discharge into rivers, lakes, and oceans. Currently, there are a variety of water purification technologies, such as adsorption, chemical precipitation, ion exchange, reverse osmosis, and electrochemical treatment. Among them, adsorption has become a promising solution due to its high efficiency, low cost, and ease of operation. Most of the adsorbents that have been studied are in powder and film form. These two forms of adsorbents have the following defects: First, the powdered adsorbent has a large specific surface area, but it is difficult to recycle, which is not conducive to the application of practical water treatment; second, the film adsorbent material is too thin. Although the ability to adsorb pollutants per unit weight is strong, the one-time adsorption capacity of the film material is not large enough, and it is easy to break in practical applications. Due to the effectiveness, low cost, eco-friendliness, and biodegradability of biomass-based adsorbents, and also under the call of the American Chemical Society's "green chemistry" concept, the use of biomass-based adsorbents in the field of water treatment is more attractive than other adsorbents. Therefore, it is urgent to develop a biomass-based adsorbent with large adsorption capacity, simple preparation method and easy recovery to overcome the limitations of existing adsorbents. Summary of the invention

[0003] The purpose of the present invention is to avoid the shortcomings of the prior art and provide a soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure, which can not only efficiently adsorb oil and dye pollutants, but also be reused, and also has the advantages of being environmentally friendly and low cost.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure is provided, which is prepared by the following method, wherein the method comprises the following steps:

[0006] Step 1, dissolving polyvinyl alcohol in anhydrous dimethyl sulfoxide to obtain a polyvinyl alcohol solution, cooling the solution to room temperature, and then sequentially adding succinic anhydride and triethylamine and performing a mixing reaction to obtain a carboxylated polyvinyl alcohol solution;

[0007] Step 2, adding 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide to the carboxylated polyvinyl alcohol solution, stirring and reacting, then adding dopamine hydrochloride and triethylamine, and continuing the reaction at room temperature and nitrogen to obtain a dopamine-grafted polyvinyl alcohol solution;

[0008] Step 3, dialyzing and concentrating the dopamine-grafted polyvinyl alcohol solution to obtain a dopamine-grafted polyvinyl alcohol concentrated solution;

[0009] Step 4: adding the soy protein isolate into the dopamine-grafted polyvinyl alcohol concentrated solution, quantitatively adding deionized water, then adding glycerol and mixing evenly, adjusting the pH to 9-11, continuing to stir evenly and then freeze-drying to obtain a composite;

[0010] Step 5: Evenly mix methyltrimethoxysilane and n-hexane to obtain a mixed soaking solution, add the complex into the mixed soaking solution and soak it, and then dry it in an oven to obtain a soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure.

[0011] In some embodiments, in step 1, the weight ratio of polyvinyl alcohol, anhydrous dimethyl sulfoxide solution, succinic anhydride and triethylamine is 1-3:60-120:0.2-0.8:0.2-0.8.

[0012] In some embodiments, in step 2, the weight ratio of the carboxylated polyvinyl alcohol solution, the 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, dopamine hydrochloride and triethylamine is 90-120:0.5-10:0.3-0.6:0.5-1:0.2-0.6.

[0013] In some embodiments, in step 4, the ratio of the quantified volume of deionized water to the volume of glycerol is 10:0.1-0.5.

[0014] In some embodiments, in step 1, the mixing reaction time is 20 to 30 hours.

[0015] In some embodiments, in step 2, the reaction is continued for 20 to 30 hours at room temperature.

[0016] In some embodiments, in step three, the dialyzed dopamine-grafted polyvinyl alcohol solution is concentrated by rotary evaporation to a concentration of 4 to 5 times the original concentration of the dopamine-grafted polyvinyl alcohol solution.

[0017] In some embodiments, in step 4, stirring is performed in a magnetic stirrer and the stirring time is 0.5 to 2 hours.

[0018] In some embodiments, the composite is immersed in the mixed immersion solution for 1 to 3 hours.

[0019] In some embodiments, in step five, the drying temperature in the oven is 50-70°C.

[0020] The beneficial effects of the soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure of the present invention are as follows:

[0021] (1) The soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure of the present invention has a soy protein / polyvinyl alcohol-dopamine mixed liquid. During the freezing process, water molecules gradually move slowly and gather in an orderly manner due to the interaction of hydrogen bonds. Therefore, the soy protein / polyvinyl alcohol-dopamine mixed liquid forms an ice crystal structure during the molding process, so that during the vacuum freeze-drying process, ice crystals sublimate, and pores are formed at the positions of ice crystals, thereby forming a three-dimensional interconnected porous material, which is conducive to the adsorption and retention of oil products (toluene, kerosene, hydraulic oil and soybean oil). By adjusting the amount of ice crystals, the density of the composite sponge can be achieved to 0.1g / cm 3 , so that the composite sponge can float on the water surface after absorbing the oil, which is conducive to the rapid recovery of the composite sponge after water treatment, and also makes the pore surface area of ​​the composite sponge reach 0.75m 2 / g, the porosity can reach 92%, the total pore volume can reach 11mL / g, and the saturation capacity for adsorbing oil is larger.

[0022] (2) The soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure of the present invention has dopamine grafted onto polyvinyl alcohol to obtain an elastic structure. The elastic structure is added to the soy protein isolate, which effectively improves the brittleness of the soy protein isolate itself. The two components of soy protein isolate and polyvinyl alcohol-dopamine can be prepared into a composite sponge with elastic characteristics, which can be reused after adsorbing oil and squeezing.

[0023] (3) The soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure of the present invention has phenolic hydroxyl and carboxyl functional groups due to the grafting of succinic anhydride and dopamine. The presence of the two acidic groups, carboxyl and phenolic hydroxyl, enables the material to ionize H in aqueous solution. + Under electrostatic interaction, the anionic functional groups produced have a stronger selective adsorption effect on cationic dyes (methylene blue), which is beneficial to the adsorption of cationic dyes and increases the dye adsorption capacity.

[0024] (4) The invented soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure, the soybean protein isolate is an amphiphilic substance, which is not only lipophilic, but also can adsorb dyes dissolved in water media.

[0025] (5) The invented soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure uses soy protein isolate, polyvinyl alcohol and dopamine as biomass raw materials, does not need to rely on petrochemical products, avoids secondary pollution, is cheap, renewable, and easily degradable, and is suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The synthetic flow chart of SPI / PVA-DP composite material with sponge structure;

[0027] Figure 2 To compare the adsorption performance of SPI / PVA-DP composite materials with sponge structure to different oils;

[0028] Figure 3 The oil-water separation efficiency diagram of SPI / PVA-DP composite material with sponge structure for different oil products;

[0029] Figure 4 This is the adsorption capacity diagram of methylene blue dye by SPI / PVA-DP composite material with sponge structure;

[0030] Figure 5 The pore size distributions of three SPI / PVA-DP composites with sponge structure;

[0031] Figure 6 (a) XPS spectra of PVA, DP and PVA-DP; (b) ATR-FTIR spectra of PVA and PVA-DP; (c), (e) and (g) are the C1s curve fitting results of pure PVA, pure DP and PVA-DP, respectively; (d), (f) and (h) are the N1s curve fitting results of pure PVA, pure DP and PVA-DP, respectively;

[0032] Figure 7 This is the SEM image of the shear surface of SPI / PVA-DP with sponge structure;

[0033] Figure 8 are the compressive stress-strain curves of SPI / PVA and SPI / PVA-DP composites at 50% strain;

[0034] Fig. 9 The appearance of SPI / PVA and SPI / PVA-DP under 90% compressive strain. DETAILED DESCRIPTION

[0035] The preferred embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the preferred embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0036] Example

[0037] The soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure disclosed in this embodiment is as follows Figure 1 As shown, it is prepared by the following method, which comprises the following steps:

[0038] Step 1, dissolving polyvinyl alcohol in anhydrous dimethyl sulfoxide to obtain a polyvinyl alcohol solution, cooling the solution to room temperature, and then sequentially adding succinic anhydride and triethylamine and performing a mixing reaction to obtain a carboxylated polyvinyl alcohol solution;

[0039] First, polyvinyl alcohol (PVA) is dissolved in anhydrous dimethyl sulfoxide (DMSO). Polyvinyl alcohol can be dissolved in DMSO because DMSO is a strong polar solvent that can form hydrogen bonds with the hydroxyl groups in polyvinyl alcohol, helping the polyvinyl alcohol to dissolve.

[0040] The polyvinyl alcohol-DMSO solution obtained above is cooled to room temperature for the convenience of subsequent reactions. Succinic anhydride is added to the cooled mixed solution. Succinic anhydride is a commonly used carboxylic anhydride, which can react with the hydroxyl group in polyvinyl alcohol to introduce a carboxyl functional group. After adding succinic anhydride, triethylamine is further added. Triethylamine may be used as a catalyst or acid binding agent here to promote the reaction of succinic anhydride and polyvinyl alcohol to form carboxylated polyvinyl alcohol. After adding triethylamine, the mixed solution needs to be fully stirred to ensure the uniformity of the reaction, to ensure the completeness of the carboxylation reaction, and the obtained carboxylated polyvinyl alcohol. This modified polyvinyl alcohol has more carboxyl functional groups, which can improve its water solubility and cross-linking reactivity and other properties.

[0041] Step 2, adding 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide to the carboxylated polyvinyl alcohol solution, stirring and reacting, then adding dopamine hydrochloride and triethylamine, and continuing the reaction at room temperature and nitrogen to obtain a dopamine-grafted polyvinyl alcohol solution;

[0042] 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS) are added to carboxylated polyvinyl alcohol. EDC·HCl and NHS are commonly used carboxyl activation reagents. EDC·HCl can react with carboxyl groups to form active intermediates, which then react with NHS to form NHS ester intermediates. After adding EDC·HCl and NHS, the mixed solution needs to be stirred to promote the reaction. Subsequently, dopamine hydrochloride and triethylamine are added to the reaction system. Dopamine hydrochloride provides dopamine molecules, while triethylamine acts as a base catalyst to promote the reaction of NHS esters with primary amine groups in dopamine molecules to form stable amide bonds. After adding dopamine hydrochloride and triethylamine, the reaction is continued to be stirred at room temperature and nitrogen environment conditions to ensure that the dopamine molecules can fully react with the NHS esters to form dopamine-grafted polyvinyl alcohol.

[0043] Step 3, dialyzing and concentrating the dopamine-grafted polyvinyl alcohol solution to obtain a dopamine-grafted polyvinyl alcohol concentrated solution;

[0044] Dialysis can remove unreacted monomers, low molecular weight polymers, and small molecule impurities in the solution. This process usually takes 2 days to ensure the dialysis effect. After the dialysis treatment is completed, the dopamine-grafted polyvinyl alcohol solution will be transferred to a rotary evaporator. By reducing the pressure and heating, the solvent (usually water) in the solution will evaporate, thereby increasing the concentration of dopamine-grafted polyvinyl alcohol in the solution. This process can effectively reduce the volume of the solution and remove unnecessary impurities to obtain a high-concentration dopamine-grafted polyvinyl alcohol solution.

[0045] Step 4: adding the soy protein isolate into the dopamine-grafted polyvinyl alcohol concentrated solution, quantitatively adding deionized water, then adding glycerol and mixing evenly, adjusting the pH to 9-11, continuing to stir evenly and then freeze-drying to obtain a composite;

[0046] A certain amount of deionized water is added to the solution to adjust the concentration and viscosity of the solution to a state suitable for subsequent processing. Glycerol can improve the plasticity of the material by weakening the forces between polymer molecular chains and increasing the mobility of the molecular chains. After all components are added, the mixed solution needs to be fully stirred to ensure that the components are evenly distributed to form a uniform mixed solution. The pH value of the solution is adjusted to 9-11 by adding alkaline substances (such as sodium hydroxide). This pH range helps the dissolution of proteins and the stability of dopamine-grafted polyvinyl alcohol. After adjusting the pH, continue to stir the solution to ensure that the pH adjuster is evenly distributed and the solution remains uniform. The uniform mixed solution is freeze-dried. Freeze-drying is a method of removing water from the solution under low temperature and vacuum conditions, which can maintain the microstructure and active ingredients of the material and avoid the destruction of heat-sensitive ingredients. At the same time, the removal of water will cause the material to form a porous structure at the location of the original ice crystals.

[0047] Step 5: Evenly mix methyltrimethoxysilane and n-hexane to obtain a mixed soaking solution, add the complex into the mixed soaking solution and soak it, and then dry it in an oven to obtain a soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure.

[0048] After the above steps, a soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure is obtained. This material combines the characteristics of soy protein, polyvinyl alcohol and dopamine, and provides a high specific surface area and porosity through a sponge structure.

[0049] The process involves multiple steps such as surface modification, freeze drying, soaking treatment and heat treatment of the material, and ultimately produces a composite material with a specific structure and properties. The sponge structure of this material may help improve its adsorption performance in water treatment.

[0050] In this embodiment, in step 1, the weight ratio of polyvinyl alcohol, anhydrous dimethyl sulfoxide solution, succinic anhydride and triethylamine is 1-3:60-120:0.2-0.8:0.2-0.8, preferably 2.2:108:0.5:0.5.

[0051] In this embodiment, in step 2, the weight ratio of the carboxylated polyvinyl alcohol solution, the 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, dopamine hydrochloride and triethylamine is 90-120:0.5-10:0.3-0.6:0.5-1:0.2-0.6, preferably 111:0.9:0.5:0.9:0.5.

[0052] In this embodiment, in step 4, the ratio of the volume of deionized water after quantification to the volume of glycerol is 10:0.1-0.5, preferably 10:0.2. The specific parameters can be selected according to actual conditions, and are not limited to uniqueness here.

[0053] In this embodiment, in step 1, the mixing reaction time is 20 to 30 hours, preferably 24 hours. The specific parameters can be selected according to actual conditions and are not limited here.

[0054] In the embodiment, in step 2, the reaction time at room temperature is 20 to 30 hours, preferably 24 hours. The specific parameters can be selected according to actual conditions and are not limited here.

[0055] In this embodiment, in step 3, the dialyzed dopamine-grafted polyvinyl alcohol solution is concentrated by rotary evaporation to 4 to 5 times its original concentration. Specific parameters can be selected according to actual conditions and are not limited here.

[0056] In this embodiment, in step 4, stirring is performed in a magnetic stirrer for 0.5 to 2 hours, preferably 1 hour. Specific parameters can be selected according to actual conditions and are not limited to a uniqueness here.

[0057] In this embodiment, the freeze-dried complex is immersed in the mixed immersion solution for 1 to 3 hours, preferably 2 hours. Specific parameters can be selected according to actual conditions and are not limited here.

[0058] In this embodiment, in step 5, the drying temperature in the oven is 50-70° C., preferably 60° C. The specific parameters can be selected according to actual conditions, and are not limited to a uniqueness here.

[0059] Effect verification:

[0060] In order to further verify the characteristics and functions of the soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure of the present invention, test examples and comparative examples were carried out respectively.

[0061] The abbreviations of the components are as follows:

[0062] SPI / PVA-DP Soy Protein Isolate / Polyvinyl Alcohol-Dopamine

[0063] SPI / PVA soy protein isolate / polyvinyl alcohol

[0064] SPI Soy Protein Isolate

[0065] PVA polyvinyl alcohol

[0066] DP dopamine

[0067] Test example

[0068] Step 1, synthesis of carboxylated PVA. PVA (2.2 g, 50 mmol AOH group) was dissolved in anhydrous DMSO (100 mL), and the solution was cooled to room temperature. Succinic anhydride (0.5 g, 5.0 mmol) and triethylamine (0.5 g, 5.0 mmol) were added in sequence, and the reaction was continued for 24 h to obtain carboxylated PVA;

[0069] Step 2: 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC HCl) (957.8 mg, 5.0 mmol) and N-hydroxysuccinimide (NHS) (575 mg, 5 mmol) were added to the reaction solution containing carboxyl functionalized PVA and stirred for 30 min. Then, dopamine hydrochloride (948.20 mg, 5.0 mmol) and triethylamine (505.95 mg, 5.0 mmol) were added, and the mixture was stirred at room temperature under N2 for 24 h to obtain dopamine-grafted polyvinyl alcohol (PVA-DP);

[0070] Step 3, dialyze the sample solution for 2 days, concentrate the sample solution by rotary evaporation to 4-5 times, take 2 mL of the sample solution for freeze drying, and weigh it to determine the concentration of the sample solution;

[0071] Step 4: Weigh SPI at SPI:PVA-DP weight ratios of 100:0, 80:20, 60:40, 40:60, 20:80 and 0:100 and add it to a 25 mL beaker containing PVA-DP sample solution, with a solid content of 0.3 g, and add deionized water to control the final volume to 10 mL. Add 0.2 mL of glycerol to the sample solution, and finally adjust the pH of the sample solution to 10 with 15% NaOH solution. Stir the above sample solution at room temperature for 1 h in a magnetic stirrer, take it out, and freeze-dry it.

[0072] Step 5: The freeze-dried samples were added to 20 mL of 1.5% methyltrimethoxysilane (MTMS) / n-hexane solution and soaked for 2 hours, and then dried in an oven at 60° C. to obtain a cylindrical SPI / PVA-DP product with a diameter of 30 mm and a height of 15 mm.

[0073] The soy protein / polyvinyl alcohol-dopamine composite water treatment materials with sponge structures (hereinafter referred to as sponge structures) obtained in the test examples, namely the SPI / PVA-DP composite sponges, were used to adsorb toluene, kerosene, hydraulic oil and soybean oil, and their saturated adsorption capacity, adsorption rate and reusability were compared. Figure 2(a) It can be seen that compared with commercial PP oil-absorbing felt, the 60:40, 40:60 and 20:80 soybean protein / polyvinyl alcohol-dopamine composite water treatment materials with sponge structure have a larger oil absorption capacity, which can reach up to 9.21g / g. However, 100:0, 80:20 and 0:100 are slightly inferior to PP oil-absorbing felt. Figure 2 (b), (c), (d) and (e) show that all composite sponges can almost reach full adsorption within 5 min and reach saturated adsorption capacity within 30 min. Figure 2 (f), (g), (h) and (i) indicate that the composite sponge is reusable for adsorbing different oil products. The composite sponge can be used 10 times with a recovery rate of more than 90%, and its adsorption capacity is even improved compared to the first use. Figure 3 It can be seen that the oil-water separation efficiency of the SPI / PVA-DP composite sponge for toluene, kerosene, hydraulic oil and soybean oil can reach more than 95%, so the composite sponge can be used in practical applications of oil-water separation.

[0074] In 200 μg / mL methylene blue solution, the adsorption values ​​of methylene blue by all composite sponges obtained in the test examples can reach more than 48 mg / g ( Figure 4 ), among which the composite sponges with a ratio of 100:0, 80:20 and 60:40 have higher adsorption values, which are 54.5 mg / g, 54.2 mg / g and 54.4 mg / g respectively. At the same time, the adsorption efficiency of the composite sponge for methylene blue can reach more than 85%, which shows that it has effective adsorption for cationic dyes (methylene blue). Relative to cationic dyes, the composite sponge was adsorbed in a 150μg / mL anionic dye (acid blue 92) solution for two hours, and the results showed that it could not detect its adsorption effect on acid blue 92. Obviously, the composite sponge exhibits selective adsorption for cationic dyes due to its rich anionic groups such as phenolic hydroxyl and carboxyl.

[0075] Table 1 shows the pore analysis of three SPI / PVA-DP composite sponges;

[0076]

[0077]

[0078] Figure 5The pore size distribution of three SPI / PVA-DP composite sponges with different weight ratios is shown. The 80:20 and 60:40 composite sponges showed similar average pore sizes of 61.95μm and 61.75μm, respectively, while the average pore size of the 40:60 composite sponge was 40.70μm. The porosities of the 80:20, 60:40 and 40:60 composite sponges were 91.88%, 91.15% and 89.00%, respectively. This shows that the composite sponge has a high porosity and macroporous structure. Its total pore volume and total pore surface area show that the composite sponge has a large adsorption space and adsorption surface, confirming that the composite sponge is beneficial in various applications of water treatment. As shown in Table 1, the sample density is between 0.08-0.12g / cm 3 , indicating that the composite material can be prepared using a small amount of raw materials and is lightweight and efficient.

[0079] In order to verify whether PVA is successfully grafted with DP, XPS technology ( Figure 6 ) analyzed the surface chemical changes and chemical composition. For pure PVA, C1s, O1s and N1s can be detected. The content of C and O in PVA is 68.50% and 31.20% respectively, while the content of N is only 0.30%. The N element may be a contaminant or the sample is impure. Since DP itself contains the N element, DP can detect a very strong N1s peak, which is not found in pure PVA. However, in the XPS spectrum of the sample PVA-DP, a relatively strong N1s peak appeared, and the content of C, O and N in the sample was 63.53%, 21.18% and 2.2% respectively. Obviously, the C and O contents of the target sample are lower than those of pure PVA, while the N content is increased. In addition, from the peak separation of C1s, it can be seen that a new peak belonging to C=O appears at 288.1eV. This C=O is caused by the grafting of succinic anhydride onto PVA, and C=O will also be produced when DP is subsequently grafted onto carboxylated polyvinyl alcohol. This shows that the reaction equation is valid and PVA-DP is successfully synthesized.

[0080] In the infrared spectra of PVA and PVA-DP ( Figure 6 b) at 3290 cm -1 There is a broad and strong absorption at 2920cm, which is attributed to the symmetrical stretching vibration of the -OH group; -1 The peak at 1090 cm is attributed to the CH stretching vibration peak of saturated C; -1 The peak of the CO stretching vibration of the target product PVA-DP is relatively strong compared with pure PVA, indicating that the addition of phenolic hydroxyl groups of DP increases the total number of hydroxyl groups in the target product. -1 A new peak was generated at 1650cm-1 The new peaks at 40° and 45° are the C=C stretching vibrations of the aromatic ring. The appearance of the two new peaks further confirms that DP has been successfully grafted onto PVA.

[0081] Depend on Figure 7 It can be seen that all samples have a porous structure. For the composite sponge prepared with soy protein isolate (i.e., 100:0), its pore structure is relatively simple, and there are fewer holes on the pore wall compared to the 20μm micrographs of other samples. The pore structure of other samples is very rich, especially 80:20, 60:40, and 40:60, the holes on the pore wall are very dense, and the higher the protein content, the larger the pores, indicating that the addition of soy protein isolate has a positive effect on the pore structure of the porous composite sponge.

[0082] Comparative Example

[0083] In order to compare and illustrate the effect of adding dopamine in the present invention, a comparative example of a soybean protein / polyvinyl alcohol composite sponge for water treatment is provided as follows:

[0084] At 90°C, PVA was dissolved in 10 mL of deionized water. After complete dissolution, SPI was added into a 25 mL beaker (the weight ratio of SPI:PVA was 100:0, 80:20, 60:40, 40:60, 20:80 and 0:100), with a solid content of 0.3 g. The pH of the sample solution was adjusted to 10 with 15% NaOH solution, and stirred in a magnetic stirrer at room temperature for 1 h. The product was taken out and freeze-dried to obtain a cylindrical SPI / PVA product with a diameter of 30 mm and a height of 15 mm.

[0085] Depend on Figure 8 The results show that the height of the SPI / PVA composite sponge has been reduced by more than 20% and cannot be restored after the fifth compression at 50% strain. After 10 times of 50% compression strain, the composite sponge is severely deformed, proving that it has no elasticity. However, the composite sponge grafted with dopamine only deforms slightly after 50 times of 50% compression strain, and can almost recover to its original height when the external force is released. Fig. 9 It can be seen that the SPI / PVA composite sponge has become flattened under 90% strain in the same batch and size of composite sponges. Except for 100:0, other SPI / PVA-DP composite sponges can still almost recover to their original height, indicating that most SPI / PVA-DP composite sponges have good elasticity and compression properties.

[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure, characterized in that: It is prepared by the following method, which comprises the following steps: Step 1, dissolving polyvinyl alcohol in anhydrous dimethyl sulfoxide to obtain a polyvinyl alcohol solution, cooling the solution to room temperature, and then sequentially adding succinic anhydride and triethylamine and performing a mixing reaction to obtain a carboxylated polyvinyl alcohol solution; Step 2, adding 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide to the carboxylated polyvinyl alcohol solution, stirring and reacting, then adding dopamine hydrochloride and triethylamine, and continuing the reaction at room temperature and nitrogen to obtain a dopamine-grafted polyvinyl alcohol solution; Step 3, dialyzing and concentrating the dopamine-grafted polyvinyl alcohol solution to obtain a dopamine-grafted polyvinyl alcohol concentrated solution; Step 4: adding the soy protein isolate into the dopamine-grafted polyvinyl alcohol concentrated solution, quantitatively adding deionized water, then adding glycerol and mixing evenly, adjusting the pH to 9-11, continuing to stir evenly and then freeze-drying to obtain a composite; Step 5: Evenly mix methyltrimethoxysilane and n-hexane to obtain a mixed soaking solution, add the complex into the mixed soaking solution and soak it, and then dry it in an oven to obtain a soy protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure.

2. The soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure according to claim 1, characterized in that: In step 1, the weight ratio of polyvinyl alcohol, anhydrous dimethyl sulfoxide solution, succinic anhydride and triethylamine is 1-3:60-120:0.2-0.8:0.2-0.

8.

3. The soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure according to claim 1, characterized in that: In step 2, the weight ratio of the carboxylated polyvinyl alcohol solution, the 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, dopamine hydrochloride and triethylamine is 90-120:0.5-10:0.3-0.6:0.5-1:0.2-0.

6.

4. The soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure according to claim 1, characterized in that: In step 4, the ratio of the quantified volume of deionized water to the volume of glycerol is 10:0.1-0.

5.

5. The soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure according to claim 1, characterized in that: In step 1, the mixing reaction time is 20 to 30 hours.

6. The soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure according to claim 1, characterized in that: In step 2, the reaction is continued for 20 to 30 hours at room temperature.

7. The soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure according to claim 1, characterized in that: In step 3, the dialyzed dopamine-grafted polyvinyl alcohol solution is concentrated by rotary evaporation to a concentration of 4 to 5 times the original concentration of the dopamine-grafted polyvinyl alcohol solution.

8. The soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure according to claim 1, characterized in that: In step 4, stirring is performed in a magnetic stirrer for 0.5 to 2 hours.

9. The soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure according to claim 1, characterized in that: The composite is immersed in the mixed immersion solution for 1 to 3 hours.

10. The soybean protein / polyvinyl alcohol-dopamine composite water treatment material with a sponge structure according to claim 1, characterized in that: In step 5, the drying temperature in the oven is 50-70°C.

Citation Information

Patent Citations

  • Method for preparing polyvinyl alcohol biomass composite thin film protected by branch-linear polymer brush

    CN109942870A

  • Hydrophilic modified melamine sponge as well as preparation method and application thereof

    CN115584053A

  • Soy proteins for preparation of gels, fibers and films

    US20220378713A1

Cited By

  • Soy protein / polyvinyl alcohol-dopamine composite water treatment material having sponge structure

    WO2026138020A1